In silico and in vitro analyses of the pathological relevance of the R258H mutation of hepatocyte nuclear factor 4α identified in maturity‐onset diabetes of the young type 1. Issue 3 (10th December 2018) - Sugawara, Kenji; Nomura, Kazuhiro; Okada, Yuko; Sugano, Aki; Matsumoto, Masaaki; Takarada, Toru; Takeuchi, Atsuko; Awano, Hiroyuki; Hirota, Yushi; Nishio, Hisahide; Takaoka, Yutaka; Ogawa, Wataru
Abstract: Mutations of the hepatocyte nuclear factor 4α (HNF4α) gene give rise to maturity‐onset diabetes of the young type 1. Although many such mutations have been identified in affected individuals, part of these mutations has been characterized with regard to their pathological relevance. We here identified a missense mutation (c.773G>A, p.R258H) of HNF4A in a mother and daughter with early‐onset diabetes and impaired insulin secretion. In silico simulation and in vitro luciferase reporter analyses showed that the mutation impairs the stability of self‐dimerization and the transactivation activity of HNF4α. Although arginine‐258 does not appear to participate directly in dimerization, its mutation alters the electrostatic surface potential of the dimer interface. Our results thus suggest that this mutation impairs the function of HNF4α and thereby contributes to the pathogenesis of maturity‐onset diabetes of the young type 1. Abstract : A mutation (p.R258H) of HNF4? impairs the stability of self‐dimerization and the transactivation activity. Our results suggest that this mutation impairs the function of HNF4? and thereby contributes to the pathogenesis of MODY1.